Photographers at work : essential business and production skills for photographers in editorial, design, and advertising - Evening, Martin (New Riders, 2015)
Today, being a professional photographer is about much more than the ability to make a technically perfect image, and photographers need to use many other skills that go beyond the production of a photograph. What are the relationships between photographer and clients really like? How should you prepare for a special effects shoot? What steps should you take to protect your equipment while shooting on location? In Photographers at Work, photographer and best-selling author Martin Evening examines these issues and much more, offering advice to help you succeed in an ever-changing-and challenging-field. Answers to these questions will give you the practical information and guidance you need to make it as a photographer in the creative fields of editorial, design, or advertising. This book takes an in-depth look at the industry, covering key topics that every working photographer needs to know-from working with models, to the legal and safety issues of working on location, to owning and running a studio, securing clients and work, and handling the complex finances of a business. While sharing his personal experience, Evening also introduces you to 18 working photographers and industry pros through video and written interviews in which they share their perspectives on this rapidly changing industry and offer advice to help you succeed as well. Includes links to 12 video interviews (more than 3 hours total runtime) by many of the featured photographers in the book, offering more image examples, anecdotes, and insights into the lives of working photographers. Provides access (available to all readers!) to downloadable Reader's Supplement, a 55-page guide that includes key concepts, terms and definitions, learning objectives, discussion questions, assignments, additional resources, and links to featured photographers. Focuses on all the skills a photographer needs to succeed-from handling the hidden costs of running a studio to finding and working with models to insuring a business. Offers essential tips on how to get started as a photographer, such as where to find clients and how to keep them.